Is the lack of smartphone data skewing wealth indices in low-income settings? - Poirier, Mathieu J. P.; Bärnighausen, Till; Harling, Guy; Sié, Ali; Grépin, Karen A. (Population health metrics, 2021)
Smartphones have rapidly become an important marker of wealth in low- and middle-income countries, but international household surveys do not regularly gather data on smartphone ownership and these data are rarely used to calculate wealth indices.